The precarious relationship between embodiment and digital religion - Friesen, Tobias (Poligrafi, 2024)
This article presents a critique of the prevalent notion that the digital realm is characterized by a condition of disembodiment and excarnation. In order to sub-stantiate its argument, this article initially presents an example of the discourse surrounding the disembodiment thesis, namely Richard Kearney’s considerations of touch in the digital age. In this context, the article uncovers a dominant discur-sive framing of harmonization vs. over-problematization. It then proceeds to exa-mine the work of Thomas Fuchs and his phenomenological critique of virtuality, which also emphasizes the aspect of disembodiment. Lucy Osler presents a coun-terargument to the thesis of disembodiment, simultaneously contributing to both phenomenological and embodiment research. Following Osler, this article argues that embodiment is inherently precarious and that the digital sphere requires a theory of multiple modes of embodiment rather than the creation of a dichotomy between embodiment and the digital. The article concludes with some theoretical considerations of digital religion and theological reflections on the possibility of an online Eucharist, a topic that was prevalent in Christian theology during the COVID-19 pandemic.
Keywords: breztelesnost; digital religion; digitalna religija; disembodiment; embodiment; fenomenologija; phenomenology; utelešenost